Jejak Langkah Pengadilan Agama Purwakarta - Sofia Gussevi; Melinda Maulani; Nur Aeni Muhfi (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2021)
The Footsteps of the Purwakarta Religious Court, This research is motivated by the author's concern about the lack of references used in teaching the Religious Courts course in Indonesia. This research is an implementation of one of the models used in the study of the Religious Courts in Indonesia. The model for the study of the Religious Courts in Indonesia is the Socio-Historical Assessment Model. This study focuses on the chronology of the growth and development of the judiciary including the judiciary within a certain period of time or in a certain (local) cultural area. In this case the researcher took the object of his research at the Purwakarta Religious Court. This study aims to determine the elements of changes that occur in the development of the Purwakarta Religious Court and the basis for consideration of changes in the Purwakarta Religious Court. The method used is descriptive qualitative method. Based on the results of the research, it shows that the elements of changes that have occurred in the development of the Purwakarta Religious Court are the facilities for the reform of the birography and the number of cases resolved. The basis for considering the changes in the Purwakarta Religious Court is the socio-cultural conditions of the community and the optimization of services to the community.